RELATIONSHIP BETWEEN THE POPULATION DENSITY AND THE OCCURRENCE OF DENGUE HEMORRHAGIC FEVER IN PALU AT 2010-2014 - A.R, Rahmi; Sari, Puspita (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran dan Ilmu Kesehatan, 2017)
Background:  Dengue hemorrhagic fever (DHF) represents one of public health problems in Indonesia and so do the other  countries. Commonly, DHF infections are found in tropics and subtropics  country, specially in urban and sub urban area. The number of sufferer and its distribution increases along with mobility and population density.  Methods: The study used  analytic observational method with cross sectional design. The samples  were number of  DHF cases in Palu City at 2010-2014 that recorded in Health Department of Palu. The data used in form secondary data of DHF cases through Health Department of Palu’s records and population density through Statistic of Palu City. Data processing was done with SPSS program with spearman test. Results: The results showed that r value = 0,502 and p value = 0,000 which means that there is a moderate relationship with positive direction between the population density and the occurrence of dengue hemorrhagic fever  Conclusions: There is a moderate relationship with positive direction between the population density and the occurrence of dengue hemorrhagic fever in Palu City at 2010-2014.   Key words: occurrence of DHF, population density